Unveiling Multiracial Family Parenting Practices in Early Childhood Education within the Indonesian Context: A Case Study - Aghnaita; Murniati, Wahyuni (Islamic Early Childhood Education Study Program, Faculty of Tarbiyah and Education, UIN Sunan Kalijaga Yogyakarta, 2023)
Purpose – The presence of multiracial families in society has given rise to various questions regarding early childhood care practices. It is essential for children to develop a strong sense of identity, considering their diverse cultural and racial backgrounds. This research aims to investigate the parenting practices within multiracial families during early childhood. Design/methods/approach – This research adopts a descriptive qualitative approach. The study is conducted in West Nusa Tenggara, spanning from May to November 2023. The primary data sources involve three multiracial families. Data collection methods include observations, interviews, and document analysis. Findings – The results reveal that parenting styles are intricately intertwined with the cultural and racial backgrounds of the parents, whether both the mother and father's races are considered or if one race predominates. Parenting responsibilities are shared, and gender-related issues are not visibly prominent. The parenting practices encompass fostering independence and discipline, promoting tolerance, instilling good manners, emphasizing health and hygiene, scheduling activities, granting freedom, providing sleep training, developing life skills, and encouraging literacy. Research implications/limitations – This study utilizes qualitative research methods and focuses on three multiracial families as research subjects, thereby offering insights into early childhood care. Practical implications – This research contributes to the advancement of knowledge pertaining to early childhood care within multiracial contexts. Furthermore, it serves as a valuable reference for formulating appropriate policies and educational strategies for children in multiracial families. Originality/value – Future research can delve deeper into the caregiving practices of multiracial families, considering diverse cultural and social perspectives. Paper type Case Study